Peningkatan Pemahaman Pengembangan Sosial pada Materi Tatakrama Pergaulan Melalui Layanan Orientasi Siswa Kelas IX SMP Negeri 1 Sumenep - Farid Mashudi (STKIP PGRI SUMENEP, 2020)
This research is motivated by the results of observations and experience of researchers, that students still look less able to get along and be loyal to their own friends, it happens in SMP Negeri 1 Sumenep. Students find it difficult to understand the importance of social attitudes towards their peers, what actually happens is that there is no harmony and conduciveness in class. As a result, students are judged to lack friendship. Then this study aims to, 1) describe students' social attitudes, 2) describe the implementation of orientation services in overcoming the weaknesses of students' social attitudes, 3) explain the results of orientation services towards students' social attitudes. The study was conducted using a counseling guidance action research approach (PTBK) with the research subjects of class IX students of SMP Negeri 1 SUMENEP. The study was conducted in three cycles, using instruments in the form of RPBK, observation sheets of student activities, observation sheets of research activities and questionnaires for student responses to the application of orientation service techniques. The conclusions of the results of this study are (1) through the guidance and counseling action cycle can be found effective steps in the application of orientation services to students' social development. (2) Through the counseling action cycle the application of orientation service is proven to improve students' social attitudes. Based on the conclusions of this study, it is recommended: (1) The main objectives of the service orientation of social etiquette material can be used to provide understanding and development of students' social attitudes. Therefore BK teachers as providers of counseling guidance services must prioritize processes that support the creation of a communicative, interactive atmosphere and group work in their implementation. (2) BK teachers / prospective BK teachers still need to continue to prove the application of orientation services for social etiquette material if there are students who lack social attitude.